Goiter ay iwasan para sa mabuting kalusugan Iodine deficiency aton tapnaun, goiter likawam para sa ikaayo sang aton kalawasan
Protein-energy malnutrition and micronutrient deficiencies remain as leading nutritional problems in the Philippines. Iodine Deficiency Disorder (IDD), in particular, still remains as a critical public issue in landlocked and upland areas in the country despite the passage of the ASIN Law in 1996. According to the National Nutrition Council, 35.8% of children 6-12 years old still suffer from moderate to severe IDD. After ocular surveys, focused group discussions, and preliminary iodine patch tests, the group identified that the major problem in Sition Nagpana is IDD and goiter. Therefore the group created activities that focused on improving the knowledge of the residents on proper nutrition, micronutrient deficiency with emphasis on iodine deficiency disorder, and hygiene sanitation, increasing nutritional intake of iodine in children aged 6-12 years old, and increasing awareness of ASIN Law. Medical mission was done and 11 goiter cases were identified confirming the problem of the community. To assess the components of the project, pre and post tests were done together with the Knowledge, Attitude, and Practices (KAP) Survey, 24-h our food recall, and Urinary Iodine Examination. The results for the post urinary iodine examination had a 167% increase in median urinary iodine level compared to the pre test. Also, there was an improvement in the individual pre and post test scores of the attendees thus reflecting the effectiveness of the health education lectures. The result of the evaluation shows that the Team Para sa Bayan?s Project, ?Goiter ay Iwasan Para sa Mabuting Kalusugan? was 65successful in making a Healthier and More Productive Nagpana.